ANALISIS MINAT BELAJAR DARING MATEMATIKA SISWA KOMUNITAS STUDYGRAM KELAS VII SEKOLAH MENENGAH PERTAMA - Intan Widiantika; Dadang Rahman Munandar (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This study aims to analyze the interest in learning mathematics online of students who are members of the StudyGram community and the positive impact it has. So that learning innovations can be developed using StudyGram to increase interest in learning mathematics online. The research method is descriptive research. The population in the study were 13 students of grade VII SMP who are members of the StudyGram community in Indonesia, the sample was taken by purposive sampling, with the following inclusion criteria: 1) Having a StudyGram account; 2) Class VII high school students in Indonesia. Exclusion criteria; 1) Not actively posting learning materials; 2) Not part of the StudyGram community in the WhatsApp group. The data collection technique used a scale questionnaire of students' mathematics learning interest which contained 10 statements with 7 indicators. The data analysis technique uses the formula for the percentage of students' answers and is described by the criteria for interpreting the percentage of answers. The results of the analysis show that students in the study program community have an interest in learning mathematics, this can be seen from the majority of students having an interest in learning mathematics. With this, online learning innovations can be developed using StudyGram.